A Large Eddy Simulation Study on the Effect of Devolatilization Modelling and Char Combustion Mode Modelling on the Structure of a Large-Scale, Biomass and Coal Co-Fired Flame. (1st November 2018) - Rabaçal, Miriam; Costa, Mário; Vascellari, Michele; Hasse, Christian; Rieth, Martin; Kempf, Andreas M.
Abstract : This work focuses on the impact of the devolatilization and char combustion mode modelling on the structure of a large-scale, biomass and coal co-fired flame using large eddy simulations. The coal modelling framework previously developed for the simulation of combustion in large-scale facilities is extended for biomass capabilities. An iterative procedure is used to obtain devolatilization kinetics of coal and biomass for the test-case specific fuels and heating conditions. This is achieved by calibrating the model constants of two empirical models: the single first-order model and the distributed activation energy model. The reference data for calibration are devolatilization yields obtained with predictive coal and biomass multistep kinetic mechanisms. The variation of both particle density and diameter during char combustion is governed by the conversion mode, which is modelled using two approaches: the power law using a constant parameter that assumes a constant mode during char combustion and a constant-free model that considers a variable mode during combustion. Three numerical cases are considered: single first-order reaction with constant char combustion mode, distributed activation energy with constant char combustion mode, and single first-order reaction with variable char combustion mode. The numerical predictions from the large eddy simulations are compared with experimental results of a high co-firing rate large-scale laboratory flame of coal and biomass. Furthermore, results from single particle conversion under idealised conditions, isolating the effects of turbulence, are presented to assist the interpretation of the predictions obtained with large eddy simulations. The effects of the devolatilization and conversion mode modelling on the flame lift-off, flame length, and spatial distribution and radial profiles of O2 and CO2 are presented and discussed. Both the devolatilization and conversion mode modelling have a significant effect on the conversion of particles under idealised conditions. The large eddy simulations results show that the devolatilization model has a strong impact on the flame structure, but not on the flame lift-off. On the other hand, for the tested numerical conditions, the char combustion mode model has a marginal impact on the predicted results.